Mystery Mountain - Collins, Pat; Illustrated by Canavan, Trudi (John Parsons Publishing Ltd, 2001)
Jessie is on a photography assignment at Kelemar Mountain where mysterious things are happening that make her wonder if she will be able to leave the mountain to tell her tale.
Include Color Illustration and Glossary
Keywords: Photographers -- Readers (Elementary)